Endonasal Free Flap Reconstruction Combined With Draf Frontal Sinusotomy for Complex Cerebrospinal Fluid Leak: A Technical Report & Case Series. Issue 6 (23rd August 2021) - Lee, Jake J; Wick, Elizabeth H; Chicoine, Michael R; Dowling, Joshua L; Leuthardt, Eric C; Santiago, Paul; Pipkorn, Patrik
Abstract: BACKGROUND: Frontal sinus cranialization with closure via bifrontal pericranial flaps is the gold standard for separating the nasofrontal recess from the intracranial cavity for posterior table defects. Despite the high success rate, cerebrospinal fluid (CSF) leak may persist and is particularly challenging when vascularized reconstructive options from the bicoronal incision are exhausted. OBJECTIVE: To assess a novel endonasal technique using an adipofascial radial forearm free flap delivered to the frontal recess through a Draf sinusotomy to repair complex CSF leaks from the frontal sinus. METHODS: A retrospective review of 3 patients (all male; ages 42, 43, and 69 yr) with persistent CSF leak despite frontal sinus cranialization and repair with bifrontal pericranium was performed. Etiology of injury was traumatic in 2 patients and iatrogenic in 1 patient after anaplastic meningioma treatment. To create space for the flap and repair the nasofrontal ducts, endoscopic Draf III (Case 1, 3) or Draf IIb left frontal sinusotomy (Case 2) was performed. The forearm flap was harvested, passed through a Caldwell-Luc exposure, and placed within the Draf frontal sinustomy. The flap vessels were tunneled to the left neck and anastomosed to the facial vessels by the mandibular notch. RESULTS: Intraoperatively, the flaps were well-seated and provided a watertight seal. Postoperative hospital courses were uncomplicated. There were no new CSF leaks or flap necrosis at 12, 14, and 16 mo. CONCLUSION: Endoscopic endonasal free flap reconstruction through a Draf procedure is a novel viable option for persistent CSF leak after failed frontal sinus cranialization.